Digital Transformation of Permit to Work Systems for Work at Height in High-Rise Construction Projects: A Narrative Review - Widya Ariasti; Muhammad Arrofiq (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: High-rise construction projects are high-risk activities and effective occupational safety control systems are needed. Traditional paper-based Permit to Work (PTW) systems are often plagued by delayed approvals, poor documentation and limited monitoring capability. Objective: The aim of this study is to analyze the digital transformation of PTW systems in high-rise construction projects for work-at-height activities. Method: he study was a narrative review design with 10 references from SCOPUS, Web of Science, ScienceDirect, SpringerLink, Google Scholar, and PubMed. The analysis was on electronic personal timekeeping systems, construction safety management, and occupational risk control. Result and Discussion: The review showed that website-based PTW systems enhanced approval efficiency, accessibility, integration of risk assessment, documentation management and permit traceability. Previous studies also reported high usability scores (86.9%-93.3%). But major implementation challenges are organizational readiness, workforce competency and cybersecurity issues. Conclusion: Digital PTW systems are highly promising in enhancing the management of occupational safety in work-at-height activities by improving operational efficiency, risk control, and regulatory compliance in high-rise construction projects